Steady-State Analysis and Passivity-Based Control of Single-Phase PWM Current-Source Inverters - Komurcugil, Hasan (IEEE-Inst Electrical Electronics Engineers Inc, 2010)
This paper proposes a passivity-based control (PBC) strategy for single-phase pulsewidth-modulated current-source inverters feeding a resistive load. In this strategy, it is required to estimate the load resistance and the inductor-current reference. However, the estimation accuracy depends on the inductance value when the load resistance and the inductor-current reference are estimated using an existing adaptive algorithm. In this paper, it is shown that the inductor-current reference estimation is possible at the expense of a constant reference function for the inductor current. In addition, the design of inductor and the sensitivity of the output voltage to the value of output capacitor used in the controller are studied extensively through the steady-state analysis of the proposed PBC. It is also shown that even very large values of the estimation error do not give rise to significant change in the output-voltage amplitude. Computer simulations and experiments are presented to verify the theoretical considerations.
Keywords: Current-source inverters (CSIs); passivity-based control (PBC); steady-state analysis